PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP RETURN SAHAM DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATOR (STUDI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2020) - I Putu Buda Yasa; Budi Santoso; I Nyoman Nugraha Ardana Putra (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2022)
This study aims to examine and analyze the effect of capital structure and profitability on stock returns and the ability of Good Corporate Governance to moderate the effect of capital structure and profitability on stock returns. The data analysis tool uses Moderated Regression Analysis using the Eviews program. The implication of the results of this study is that management should continue to improve effectiveness and efficiency so that banking performance continues to increase because it will have an impact on stock prices and returns. Keyword: Stock Return, Capital Structure (DER), Profitability (ROA), Good Corporate Governance (GCG).